PEMBEBASAN BEA MASUK ATAS IMPOR BUKU ILMU PENGETAHUAN BERDASARKAN PASAL 25 UU NO. 17 TAHUN 2006 Jo SKMENKEU No. 103/KMK.04/2007 - Asmorowati, Meiti (Sekolah Tinggi Hukum Bandung, 2012)
Based on article 28 paragraph (1) of 1945 Constitution, every citizen should obtain equal education. Therefore, the government has given facilities to make people obtain equal education; giving facility through free duty of imported scientific books. All scientific books can be objects of free duty of imported books, except scientific books written in Indonesian. Those books are the books which aim at improving sciences in the framework of educating nation lives. Furthermore, goods, materials for the need of research and development of science as well as carrying out a research with the aim of improving the scientific level. Free duty of imported books can be proposed by tax subjects of free duty of imported books such as institution, and university.Keywords: scientific books, objects and subjects of free duties.